Boron Oxide Nanoparticles Exhibit Minor, Species-Specific Acute Toxicity to North-Temperate and Amazonian Freshwater Fishes - MacCormack, Tyson J.; Gormley, Patrick T.; Khuong, B. Ninh; Adams, Olivia A.; Braz-Mota, Susana; Duarte, Rafael M.; Vogels, Christopher M.; Tremblay, Luc; Val, Adalberto L.; Almeida-Val, Vera M. F.; Westcott, Stephen A. (Frontiers in Bioengineering and Biotechnology, 2021)
Boron oxide nanoparticles (nB2O3) are manufactured for structural, propellant, and clinical applications and also form spontaneously through the degradation of bulk boron compounds. Bulk boron is not toxic to vertebrates but the distinctive properties of its nanostructured equivalent may alter its biocompatibility. Few studies have addressed this possibility, thus our goal was to gain an initial understanding of the potential acute toxicity of nB2O3 to freshwater fish and we used a variety of model systems to achieve this. Bioactivity was investigated in rainbow trout (Oncorhynchus mykiss) hepatocytes and at the whole animal level in three other North and South American fish species using indicators of aerobic metabolism, behavior, oxidative stress, neurotoxicity, and ionoregulation. nB2O3 reduced O. mykiss hepatocyte oxygen consumption (ṀO2) by 35% at high doses but whole animal ṀO2 was not affected in any species. Spontaneous activity was assessed using ṀO2 frequency distribution plots from live fish. nB2O3 increased the frequency of high ṀO2 events in the Amazonian fish Paracheirodon axelrodi, suggesting exposure enhanced spontaneous aerobic activity. ṀO2 frequency distributions were not affected in the other species examined. Liver lactate accumulation and significant changes in cardiac acetylcholinesterase and gill Na+/K+-ATPase activity were noted in the north-temperate Fundulus diaphanus exposed to nB2O3, but not in the Amazonian Apistogramma agassizii or P. axelrodi. nB2O3 did not induce oxidative stress in any of the species studied. Overall, nB2O3 exhibited modest, species-specific bioactivity but only at doses exceeding predicted environmental relevance. Chronic, low dose exposure studies are required for confirmation, but our data suggest that, like bulk boron, nB2O3 is relatively non-toxic to aquatic vertebrates and thus represents a promising formulation for further development.